Boli me telo? Boli me duša? Boli me! - Temnik, Sanja (Psihološka obzorja (Ljubljana), 2009)
The article reviews investigative work to date worldwide on the topic of human pain in the frame of bodily and psychological distress, as well as highlights self-destructive behaviour and suicide risk in the light of mental and somatic disorders. Our basis is a wholistic approach to human functioning,in the case of health as well as disease. Some of the common misinterpretations of expressions of mental distress are expalined and guidelines for scientific and professional work on the topic in the future are presented.
Keywords: bolečina; duševna stiska; duševne motnje; telesne motnje; depresija; somatizacija; samomor; psihologija; psychology